Three Factor Authentication using Webcam for securing Online Transaction - Hirlekar, Vaishali (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2014)
There are a continuously growing number of customers who use Online Transaction facility due to its convenience. But the security and privacy of Information may be one of the biggest concerns to the users. In face of the current security issues and the growing number of attacks and consequent frauds, new systems should be designed as to provide better authentication and identification methods. A generic and secure framework is proposed to upgrade two-factor authentication to three-factor authentication. A well designed three-factor authentication protocol authentication system can greatly improve the information assurance at low cost. In three-factor authentication, in addition to furnishing their regular password and an OTP, users will be asked to provide biometric information would irrefutably prove their identity. This fingerprint biometric information can be captured by using low cost sensors such as Web Cam. In this paper, we investigate new technique to suitably process camera images of fingertips in order to produce image which are as similar as possible to the ones coming from dedicated sensors. The proposed technique encompasses a segmentation, enhancement and matching of the fingertip image for the person’s identifiaction.